Investigation of the student-professor interaction and self-learning ability for an aerospace engineering student. Issue 12 (2021) - Castaldi, Paolo; Mimmo, Nicola
Abstract: Based on the didactic experiences of the authors as professors of Aerospace Engineering, this article proposes a mathematical model of the learning of the students in Aerospace Engineering. Starting from the definition of a taxonomy of the student's cognitive levels, a continuous-time model of the student's learning dynamics is developed. To this end, various factors linked to the nature of the student are introduced, such as inertia in learning, forgetting of concepts, readiness to educational stimuli and self-learning skills. Based on the analysis of stability and the position of the equilibrium points of the newly developed model, the characterization of the different types of the student is obtained by outlining different skills in assimilating the educational stimuli or in exploiting self-learning skills. Finally, teaching strategies are proposed based on such analysis.